Trust as state capacity: The political economy of compliance - Timothy Besley; Sacha Dray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper explores the link between trust in government, policy-making, and compliance. It focuses on a specific channel whereby citizens who are convinced that a policy is worthwhile are more motivated to comply with it. This in turn reduces the government's cost of implementing a policy and may also increase the set of feasible policies. Thus, state capacity is greater when citizens trust their government. The paper discusses alternative approaches to modelling the origins of trust, especially the link to the design of political institutions. We then provide empirical evidence consistent with the model's findings that compliance is increasing in trust using the Integrated Values Survey and voluntary compliance during COVID-19 in the UK. We also show that countries with high levels of citizen trust in government were more likely to implement policies requiring voluntary compliance during the COVID-19 pandemic. The paper suggests that trust in government can play a role in building and expanding state capacities.
Keywords: D72; E61; H11; P11; 330; state capacity; trust; government; compliance; political economy